Perbedaan Kadar Resistin Pada Obes Dengan Resistensi Insulin Dan Obes Tanpa Resistensi Insulin - Marfianti, Erlina (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2009)
Resistin is an adipocytokine that secreted from adipose tissue, resistin level serum increased in obese patients. Resistin has important biological activity on glucose and lipid metabolism, and can affect insulin resistance. Previous study suggested that high level resistin can induce insulin resistance and has contribution to impaired insulin sensitivity. The Objective of this study is to know differences of resistin level in obese with insulin resistance and obese without insulin resistance. This is a cross sectional study  with obesity patients recruited from General Check Up  and Endorinology  outpatients clinic Sardjito General Hospital Yogyakarta. Obese patients are subjects with body mass index (BMI) ≥ 25 kg/m2. Insulin resistance was assessed using HOMA-IR (homeostasis model assessment insulin resistance), formula calculated from fasting insulin and glucose levels.  Resistin  was measured with ELISA technique. Differences of obese with insulin resistance and obese without insulin resistance analyze using  Mann Whitney U test.   There was 48 subjects  analyzed in this study, 24 obese patients with insulin resistance and 24 obese patients without insulin resistance. Mean of resistin level was higher in obese subject with insulin resistance than without insulin resistance, but there was no significant (27,65±14,44 ng/ml vs 23,99±12,45 ng/ml, p= 0,37). From this research, it can be concluded that Resistin level in obese with insulin resistance higher than obese without insulin resistance, but no significant.Keywords: Resistin-Insulin Resistance-obese